Adsorption of Toll-Like Receptor 4 Agonist to Alum-Based Tetanus Toxoid Vaccine Dampens Pro-T Helper 2 Activities and Enhances Antibody Responses. (25th August 2015) - Bortolatto, Juliana; Mirotti, Luciana; Rodriguez, Dunia; Gomes, Eliane; Russo, Momtchilo
Abstract : Aluminum salts gels (alum) are TLR-independent adjuvants and have been used to boost antibody responses in alum-based vaccines such as diphtheria, pertussis, and tetanus toxoid (DPT) triple vaccine. However, the pro-Th2 activity of alum-based vaccine formulations has not been fully appreciated. Here we found that alum-based tetanus toxoid (TT) vaccine was biased toward a Th-2 profile as shown by TT-induced airway eosinophilic inflammation, type 2 cytokine production, and high levels of IgE anaphylactic antibodies. The adsorption into alum of prototypic TLR4 agonists such as lipopolysaccharides (LPS) derived from Escherichia coli consistently dampened TT-induced Th2 activities without inducing IFN γ or Th1-like responses in the lung. Conversely, adsorption of monophosphoryl lipid A (MPLA) extracted from Salmonella minnesota, which is a TIR-domain-containing adapter-inducing interferon- β - (TRIF-) biased TLR4 agonist, was less effective in decreasing Th-2 responses. Importantly, in a situation with antigenic competition (OVA plus TT), TT-specific IgG1 or IgG2a was decreased compared with TT sensitization. Notably, LPS increased the production of IgG1 and IgG2a TT-specific antibodies. In conclusion, the addition of LPS induces a more robust IgG1 and IgG2a TT-specific antibody production and concomitantly decreases Th2-cellular and humoral responses, indicating a potential use of alum/TLR-based vaccines.